Implementation of the Concept of Lifelong Education in Polish Higher Education Law before 1989. Outline of the Problem - Danuta Apanel; Tomasz Maliszewski (Wydawnictwo Naukowe Uniwersytetu Mikołaja Kopernika, 2016)
The article is a review of the regulations of higher education legislation in Poland adopted by the parliament during the twenty years between the two World Wars and in the People's Republic of Poland (1945-1989) that today could be treated as symptoms of the implementation of the concept of lifelong learning in Polish schools of higher education. An analysis of the relevant legislation was the main research method for the purpose of this article. The authors try to answer the question whether in the decades before the Third Republic of Poland there were legal solutions referring to the connections of higher education with practical implementation of the idea of lifelong education. And if, what were they? Today, when the tasks of higher education connected with the practical implementation of the idea of lifelong learning seem obvious in all European Union states, it is worth remembering that in many countries - including in Poland - the issue has a much longer tradition than just the last twenty five years. In the final parts of the article the authors also postulate comparative